MODIFICATION OF PICTURE AND PICTURE LEARNING MODEL WITH TALKING STICK SYSTEM FOR SPEAKING SKILLS - Suma Usria; Ahmad Saifudin; Siti Rofiah (IKIP Siliwangi, 2023)
This research aims to modify the cooperative learning model. The modified learning models are the picture and picture learning model and the talking stick learning model. Both models are combined to create a new learning model. This research follows the Research and Development (R&D) methodology. The development model used in this research is the ADDIE model, which consists of five steps: analysis, design, development or production, implementation or delivery, and evaluation. In this research, the stages were only carried out until the product development phase, so the effectiveness of the product has not been tested. The result of this research is a product in the form of a picture and picture learning model with a talking stick system. Additionally, the developed learning model also produces a teaching medium in the form of pictures. These pictures are used as a replacement for the stick that students will pass around. The population and sample in this research are the 7th-grade students of Excellent Ma'arif Garum Junior High School, 11 students. The data collection techniques in this research are observation, interviews, and questionnaires. The data analysis used is qualitative and quantitative. The evaluation results from the reviewers, in terms of product quality, were coded using a quantitative scale referring to the Likert scale categories of product quality. The assessment results for content validity received a percentage score of 87.5% and were categorized as very appropriate, while the assessment results for construct validity received a percentage score of 87.5% and were categorized as very appropriate. Meanwhile, the practicality aspect received a percentage score of 91.1% with a category of very appropriate. The accumulated assessment result was 88.7% with a category of very appropriate. The developed learning model is considered suitable for use in the learning process.